2018
DOI: 10.14314/polimery.2018.11.12
|View full text |Cite
|
Sign up to set email alerts
|

Release of thymol from plasticized poly(vinyl chloride)

Abstract: The aim of the study was to assess the possibility of using thymol as a potential modifier of the bioactive properties of plasticized poly(vinyl chloride) (PVC). For this purpose, a test of releasing the active substance -thymol -from modified plasticized PVC to water was performed. The higher the thymol concentration in the polymer matrix, the more substance was released during the first days of storage. The ability of the produced materials to gradually release thymol was found, which qualifies them as mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Material with 20 phr of incorporated cassia oil after 30 days of storage in water is characterised by its higher capacity to scavenge the free radical DPPH* (almost 75%). Szulc et al [ 16 ] demonstrated similar behaviour of PVC material with incorporated thymol, and Braga et al [ 8 ] described the consumption of DPPH* by PVC-based films combined with quercetin and Ag nanoparticles. High antioxidant activity was observed in the PVC-quercetin film after 24 h (60.44%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Material with 20 phr of incorporated cassia oil after 30 days of storage in water is characterised by its higher capacity to scavenge the free radical DPPH* (almost 75%). Szulc et al [ 16 ] demonstrated similar behaviour of PVC material with incorporated thymol, and Braga et al [ 8 ] described the consumption of DPPH* by PVC-based films combined with quercetin and Ag nanoparticles. High antioxidant activity was observed in the PVC-quercetin film after 24 h (60.44%).…”
Section: Resultsmentioning
confidence: 99%
“…Natural antimicrobial agents include extracts from spices such as cinnamon, allspice, clove, thyme, rosemary, and oregano, and other plant extracts such as onion, garlic, radish mustard, and horseradish [ 2 ] A number of methods of introducing essential oils into polymeric materials are being investigated. The essential oil can be incorporated into a polymer matrix or applied to a polymer film surface [ 16 ]. The following methods are known in the literature for obtaining modified material: the cast solution method [ 17 ], the encapsulation method from a polymer solution [ 18 , 19 ], or film preparation by electrospinning [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In practice, mixtures of various plasticizing substances selected in such a way that the properties of the obtained material meet the requirements of future users are often used. Despite the considerable amount of knowledge about PVC plasticization, research is still carried out to obtain and introduce into production new plasticizers that are better and better adapted to modern requirements [26][27][28][29][30][31][32][33][34][35].…”
Section: Innowacyjne Plastyfikatory Oligomeryczne Poli(chlorku Winylu) Do Aplikacji Specjalistycznychmentioning
confidence: 99%
“…Sprouts subjected to treatments that activate secondary metabolites pathways can also be a source of bioactive compounds dedicated to enriching other food products, used as pharmaceuticals, or used in other industries, e.g., in polymer processing as a source of compounds improving the thermal stability of plastics or as a compound in active or intelligent packaging [13,14,[39][40][41][42]. Nowadays, scientists are interested in improving polymer properties with essential oils, which, when incorporated into a polymer matrix or applied to a polymer film surface, can give new properties like antimicrobial or antioxidant features to the polymer [43,44]. Thermal stability can be enhanced by adding, e.g., lignin, curcuminoids, and eugenol [45][46][47].…”
Section: Introductionmentioning
confidence: 99%